2012
DOI: 10.1128/cvi.00265-12
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD8+T Cells Are Sufficient To Alleviate Impaired Host Resistance to Influenza A Virus Infection Caused by Neonatal Oxygen Supplementation

Abstract: Supplemental oxygen administered to preterm infants is an important clinical intervention, but it is associated with life-long changes in lung development and increased sensitivity to respiratory viral infections. The precise immunological changes caused by neonatal oxygen treatment remain poorly understood. We previously reported that adult mice exposed to supplemental oxygen as neonates display persistent pulmonary inflammation and enhanced mortality after a sublethal influenza A virus infection. These chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…It extends previous work showing that neonatal hyperoxia promotes fibrotic disease after infection with a sublethal dose of influenza A virus (21,22,33,34). Our findings suggest that individuals born prematurely and exposed to hyperoxia may be at increased risk for developing pulmonary fibrosis when their respiratory epithelium is damaged later in life.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It extends previous work showing that neonatal hyperoxia promotes fibrotic disease after infection with a sublethal dose of influenza A virus (21,22,33,34). Our findings suggest that individuals born prematurely and exposed to hyperoxia may be at increased risk for developing pulmonary fibrosis when their respiratory epithelium is damaged later in life.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the effects on neutrophil recruitment were more pronounced than when hyperoxia-exposed mice were infected with a sublethal dose of influenza A virus (HKx31, H3N2), wherein the increased percentage of neutrophils was similar to that of macrophages and lymphocytes (21). Subsequent studies revealed that neonatal hyperoxia did not impair the cytotoxic effects of CD8 1 T cells or memory T cells (33). Instead, neonatal hyperoxia reduced the epithelial expression of eosinophil-associated RNase (Ear)1, an antiviral RNase that inhibits viral replication, and this was associated with greater epithelial injury (34).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the work reported herein used only a single strain of influenza A virus. We have previously shown that host resistance of adult mice to several different strains of influenza virus, including HKx31 (H3N2), A/CA/04/09 (H1N1), and A/PR/8/34 (H1N1), was similarly reduced by exposure to neonatal hyperoxia (18). Therefore, while our findings do not address the role of MCP-1 or EC-SOD during infection with other strains of influenza virus (or in other strains of mice), identification of these pathways within this system improves our understanding of why individuals born preterm are at increased risk for respiratory disease later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Although vascular changes were not observed at this age, microvessel pruning and rarefaction, cardiac hypertrophy, and reduced survival were observed by 1 year of age (22). Analogous to children born prematurely, young adult mice exposed to hyperoxia as neonates also exhibit an altered host response to influenza A virus infection (21,23,24). Because this model of neonatal hyperoxia phenotypically recapitulates human diseases attributed to prematurity, it may provide an opportunity to understand how a high-oxygen environment at birth permanently alters lung development.…”
mentioning
confidence: 98%